Size-Induced Depression of First-Order Transition Lines and Entropy Jump in Extremely Layered Nanocrystalline Vortex Matter - Dolz, M.I. (2015)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina